Performance analysis of contention access period of IEEE 802.15.3 MAC protocol. (30th July 2013) - Ullah, Sana; Chen, Min; Alsalih, Waleed
IEEE 802.15.3 is expected to play a significant role in the Internet of Things (IoT). It is developed for high–rate communication between low–power devices in a Wireless Personal Area Network (WPAN). The standard defines Medium Access Control (MAC) and physical layer protocols that support real–time communication over an area of ten square metres. IEEE 802.15.3 MAC consists of a combination of Carrier Sense Multiple Access/Collision Avoidance (CSMA/CA) and Time Division Multiple Access (TDMA) protocols. The channel is divided into superframe structures where each superframe consists of a beacon, a Contention Access Period (CAP) and a Channel Time Allocation Period (CTAP). In this paper we analyse the performance of the CAP period using both analytical and simulation–based methods. We simulate CSMA/CA protocol in the CAP period using NS–2. The simulation results are compared with those obtained from analytical approximations in terms of different parameters including throughput and optimal CAP periods.